(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores the concept of «happiness» in the Uzbek and English languages through a linguo cultural lens. The article investigates the semantic structures, cultural influences, and metaphorical representations that shape how happiness is perceived and articulated in each language. The findings reveal both universal themes and culturally specific nuances, enriching our understanding of cross-cultural conceptualization.